2016
DOI: 10.12944/cwe.11.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soil and Water Conservation Practices in Central North Plateau Zone of Odisha

Abstract: The present study was undertaken in two village Tentuli and Talachampei of Keonjhar district of Odisha which come under the central north plateau zone. This zone is characterized by hilly upland area with reduced moisture holding capacity. Therefore an attempt has been made to study the various soil and water conservation practices on cost and return of crop production, to identify factors affecting yield of crops with different treatments and to study the farmer's perception of conservation agriculture produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The result supports the establishment of the relationship between climate change and mean yield and suggests the promotion of zaï þ mulch practice in soil restoration that could be expected to affect the population of Southwest of Niger in a variety of ways. With regard to the performance of this practice, several authors, such as [29,70], found that zaï þ mulch is becoming more attractive because it minimized year to year yield variation (maximizes yield stability) under a changing climate. This could be explained by the fact that it maintains soil temperature lower.…”
Section: Discussionmentioning
confidence: 99%
“…The result supports the establishment of the relationship between climate change and mean yield and suggests the promotion of zaï þ mulch practice in soil restoration that could be expected to affect the population of Southwest of Niger in a variety of ways. With regard to the performance of this practice, several authors, such as [29,70], found that zaï þ mulch is becoming more attractive because it minimized year to year yield variation (maximizes yield stability) under a changing climate. This could be explained by the fact that it maintains soil temperature lower.…”
Section: Discussionmentioning
confidence: 99%